2020
DOI: 10.1200/jco.19.02699
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Text Messaging to Reduce Early Discontinuation of Adjuvant Aromatase Inhibitor Therapy in Women With Early-Stage Breast Cancer: SWOG S1105

Abstract: PURPOSE Nonadherence to aromatase inhibitors (AIs) for breast cancer is common and increases the risk of recurrence. Text messaging increases adherence to medications for chronic conditions. METHODS We conducted a randomized clinical trial of text messaging (TM) versus no text messaging (No-TM) at 40 sites in the United States. Eligible patients were postmenopausal women with early-stage breast cancer taking an AI for > 30 days with a planned duration of ≥ 36 months. Test messages were sent twice a week ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 26 publications
0
72
0
Order By: Relevance
“…Patients and their medical team members might have differing perspectives on the definition of a "well-tolerated" medication and on measures of quality of life [52,53], but efforts must be made to better understand the patient's point of view. There are a variety of conceptual framework models such as decision support and needs, symptom management, symptom experience, self-management, and patient activation [31,[53][54][55][56]] that can be applied to improve adherence [57,58]. For example, a recent pilot program demonstrated that patient activation did not improve oral oncolytic adherence; however, patients who completed the program did report increased confidence in their ability to self-manage symptoms and seek help when experiencing side effects [55].…”
Section: Discussionmentioning
confidence: 99%
“…Patients and their medical team members might have differing perspectives on the definition of a "well-tolerated" medication and on measures of quality of life [52,53], but efforts must be made to better understand the patient's point of view. There are a variety of conceptual framework models such as decision support and needs, symptom management, symptom experience, self-management, and patient activation [31,[53][54][55][56]] that can be applied to improve adherence [57,58]. For example, a recent pilot program demonstrated that patient activation did not improve oral oncolytic adherence; however, patients who completed the program did report increased confidence in their ability to self-manage symptoms and seek help when experiencing side effects [55].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, neither version of the app was equipped to send questionnaires, and calls from nurse specialists were not intended. We can only speculate regarding how far occasional push notifications, ample choice of symptoms, and listing of frequently selected "favorites" or "last used" symptoms might have influenced patients' motivation and input selection, as unfortunately, we did not include these variables in our end-of-study assessment [18,19]. However, the increasingly careful symptom recording provided by ePROs, along with improved symptom management in routine outpatient care, demonstrated a reduction in both unplanned hospitalizations and disease burden [2].…”
Section: Discussionmentioning
confidence: 99%
“…The phase II Triumph-T trial showed excellent local tumor control (albeit short median follow up) and breast cosmesis using a 3-fraction breast brachytherapy technique, and a similar 4-fraction regimen had excellent cosmesis with no locoregional recurrences at 6 years (37, 39). Furthermore, in elderly patients, single fraction regimens have also demonstrated excellent oncologic outcomes (40), and a recent study comparing PBI to PBI plus endocrine therapy or endocrine therapy alone in women over the age of 70 with low-risk, hormone-J o u r n a l P r e -p r o o f positive early-stage breast cancer demonstrated that PBI was superior when compliance with endocrine therapy was poor (41) and tested compliance interventions have demonstrated no improvement (42,43).…”
Section: Breast Brachytherapymentioning
confidence: 99%
“… 37 , 39 Furthermore, in elderly patients, single-fraction regimens have also demonstrated excellent oncologic outcomes, 40 and a recent study comparing PBI with PBI + hormone therapy or hormone therapy alone in women age >70 years with low-risk, hormone-positive, early stage breast cancer demonstrated that PBI was superior when compliance with hormone therapy was poor, 41 and tested compliance interventions have demonstrated no improvement. 42 , 43 …”
Section: Breast Brachytherapymentioning
confidence: 99%